Adalimumab therapy in hepatitis B virus-negative polyarteritis nodosa: A case report. Issue 25 (June 2018) - Wang, Chrong-Reen; Yang, Chao-Chun
Abstract: Introduction: Polyarteritis nodosa( PAN) is a difficult-to-treat rheumatology disorder, and biologic agents have been used in such patients with a treatment failure or the disease relapse. Case presentation: We report a 42-year-old male Han Chinese who received adalimumab (ADA) alone during his vasculitis relapse, manifesting with weight loss, ankle arthritis, testicular inflammation and new-onset hypertension. Under the ADA 40 mg biweekly subcutaneous injection, there were the disappearance of clinical activity and no disease flares with a follow-up period of 26 months. Conclusion: The clinical observation in this patient suggests a potential efficacy of ADA therapy in controlling the disease activity of PAN.